Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.ijid.2020.09.1440
|View full text |Cite
|
Sign up to set email alerts
|

Acute pericarditis and severe acute respiratory syndrome coronavirus 2: Case report

Abstract: Highlights Pericarditis may be a dominant manifestation of SARS-CoV-2 infection. In a patient with chest pain, normal coronary angiogram and ST elevation on ECG we should think of pericarditis. Basic clinical tools in the setting of COVID19 epidemic should not be forgotten and may be of great help.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 14 publications
(30 reference statements)
0
23
0
11
Order By: Relevance
“…In the past months, few papers described cases of pericardial involvement in COVID-19 patients, either in association with myocarditis or as isolated manifestation [ 8 , 43 – 46 ].…”
Section: Pericarditismentioning
confidence: 99%
“…In the past months, few papers described cases of pericardial involvement in COVID-19 patients, either in association with myocarditis or as isolated manifestation [ 8 , 43 – 46 ].…”
Section: Pericarditismentioning
confidence: 99%
“…Interestingly, 45.6% of the patients had a mild pericardial effusion. Pericardial effusion incidence has not been thoroughly evaluated in Covid-19 [34,35]. In addition, troponin levels were elevated on ICU admission, a nding that has been linked to myocardial involvement in Covid-19 [3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Post-mortem studies have identified pericarditis in about 20% of the COVID-19 cases [ 50 , 51 ] and several case reports reported acute pericarditis in patients with SARS-CoV-2 infection with typical ECG signs (diffuse ST elevation and PR depression) [52] , [53] , [54] , [55] , [56] .…”
Section: “Typical” Ecg Features Of Covid-19 Complicationsmentioning
confidence: 99%